The attributes of residence/workplace areas and transit commuting - Bumsoo Lee; Peter Gordon; James E. Moore; Harry W. Richardson (Journal of Transport and Land Use)
Area type matters when we try to explain variations in public transit commuting; workplace (commuting destination) type matters more than residence (origin) type. We found this statistical link over a sample of all census tracts in the four largest California metropolitan areas: Los Angeles, San Francisco, San Diego, and Sacramento. In this research, we used a statistical cluster analysis to identify twenty generic residence neighborhood types and fourteen workplace neighborhood types. The variables used in the analysis included broad indicators of location and density, street design, transit access, and highway access. Once identified, the denser neighborhoods had higher transit commuting, other things equal. Yet what distinguishes this research is that we did not use a simple density measure to differentiate neighborhoods. Rather, density was an important ingredient of our neighborhood-type definition, which surpassed simple density in explanatory power.